The Transaction Costs Perspective on Costs And Benefits of Government Regulation - Frank A.G. den Butter; Marc de Graaf; André Nijsen (Tinbergen Institute, 2009)
This paper explores the feasibility to extend the Standard Cost Model (SCM) for calculating the costs of government regulation by taking all transaction costs into account which stem from the principal/agent relationship between regulatory authorities and economic entities. From that perspective these transaction costs do not only relate to the bonding costs of the regulated entities – part of these costs can be regarded as the administrative burden of regulation for the private sector – but also to the monitoring costs of the regulators and to the residual loss. These latter costs can be regarded as cost to society due to e.g. miscommunication on the aims of regulation, and are, of course, hard to quantify. A cost calculation using the (extended) SCM presumes that the regulatory rules are given and set autonomously by the regulatory authorities. However, it may be welfare enhancing if regulations are fashioned in such a way that net benefits are optimized. From that perspective the paper looks at the possibility to select optimal regulation by means of a cost benefit analysis. A major argument is that the benefits of regulatory measures, e.g. to internalize external effects, comprise avoiding societal costs associated with no or less regulation.
Keywords: D73; D78; H11; H83; 330; bonding costs; compliance costs; monitoring costs; welfare effects of government regulation; Folgekosten; Transaktionskosten; Wohlfahrtsanalyse; Prinzipal-Agent-Theorie